A STUDY ON THE SEROPREVALENCE OF BRUCELLOSIS IN HUMAN AND GOAT POPULATIONS OF DISTRICT BHIMBER, AZAD JAMMU AND KASHMIR - Din; A. M. U.; S. A. Khan; I. Ahmad; R. Rind; T. Hussain; M. Shahid; S. Ahmed (Journal of Animal and Plant Sciences, 2013)
The present study was design to determine the seroprevalence of brucellosis in human and goat population. A total of 300 blood samples, comprising of 150 each from goats and humans were randomly collected from District Bhimber Azad Jmmu and Kashmir. Out of the 150 blood samples 75 were collected from each males and females. The serumsamples were tested for the presence of anti-Brucella antibodies by Rose Bengal Plate Test (RBPT), Serum Plate Agglutination Test (SPAT) and Serum Tube Agglutination Test (STAT). The overall prevalence of brucellosis in goats was recorded as 13.33%, 11.33% and 9.33% by RBPT, SPAT and STAT, respectively and in humans was found to be 9.33%, 7.33% and 6.0% by RBPT, SPAT and STAT, respectively. The sex-wise prevalence of brucellosis in male goats was recorded as 10.66%, 8.0% and 6.66% by RBPT, SPAT and STAT, respectively; while in females it was 16.0%, 14.66% and 12.0% by RBPT, SPAT and STAT respectively. In males of human, the seroprevalence of brucellosis was recorded 6.66%, 5.33%, and 4.0%, whereas in females it was 12.0%, 9.33% and 8.0% by RBPT, SPAT and STAT, respectively. The prevalence of brucellosis was relatively higher in goats as compared to humans, irrespective of techniques used. It was also concluded that brucellosis was higher in females than in males in both goats and humans. Among all the serological tests applied in the present study, RBPT was found to be more sensitive and showed higher prevalence of brucellosis in goat as well as in human populations.
Keywords: Brucella; Seroprevalence; Antibody Titre; Rose Bengal Plate Test; Serum Tube Agglutination Test; Serum